2021
DOI: 10.1021/acs.jafc.0c08144
|View full text |Cite
|
Sign up to set email alerts
|

Novel Urinary Biomarkers of Orange Juice Consumption, Interindividual Variability, and Differences with Processing Methods

Abstract: Untargeted metabolomics identified urinary biomarkers able to discriminate between the intake of fresh hand-squeezed and industrially processed orange juices. Processing led to an upregulation in the excretion of hydroxy-polymethoxyflavone sulfates, abscisic acid, and sinapic acid 4′-glucuronide. The demethylated polymethoxyflavone metabolites were produced with a significant interindividual variability suggesting that they could originate from gut microbiota metabolism. No correlation between the excretion le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Tomás-Navarro et al found that the main flavanones detected in urine were phase II conjugated derivatives of naringenin and hesperetin after ingesting 400 ml of citrus fruit (orange and mandarin). 23 Previous studies from the European Prospective Investigation into Cancer (EPIC) 53,58 and PREDIMED-Plus showed that flavonoids were the main contributors to total (poly)phenol intake in the Spanish population. 54,55 On average, the consumption of citrus fruit was 151 g per day (around 35% of the total mean fruit intake) in our population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tomás-Navarro et al found that the main flavanones detected in urine were phase II conjugated derivatives of naringenin and hesperetin after ingesting 400 ml of citrus fruit (orange and mandarin). 23 Previous studies from the European Prospective Investigation into Cancer (EPIC) 53,58 and PREDIMED-Plus showed that flavonoids were the main contributors to total (poly)phenol intake in the Spanish population. 54,55 On average, the consumption of citrus fruit was 151 g per day (around 35% of the total mean fruit intake) in our population.…”
Section: Discussionmentioning
confidence: 99%
“…13 Third, the flavonoid metabolites evaluated in this study were limited and therefore influence our conclusions, but the flavanone metabolites used in the present study are well correlated with citrus fruit intake, and they have been suggested as biomarkers of citrus consumption. 23,55,57…”
Section: Papermentioning
confidence: 99%
See 2 more Smart Citations
“…After the last intake, a urine sample was collected and immediately stored at −20 °C, until analysis . Institutional ethical approvals were unnecessary as the experiments were carried out with freely available foodstuff, and only urine samples were collected, as advised by the Ethical Committee for previous studies . The volunteers gave written informed consent.…”
Section: Materials and Methodsmentioning
confidence: 99%